An ergonomic modification of the American position for laparoscopic cholecystectomy in a rural setting - Umman, Philip; Menezes, Clyde R.; Bosco, Ashish; Menon, Nandakumar (International Surgery Journal, 2019)
Laparoscopic cholecystectomy (LC) is the gold standard for the treatment of symptomatic gallstone disease. As a result of the significant investments in setting up a laparoscopy unit and training nursing staff in laparoscopic techniques, the cost of laparoscopic surgery is higher. However, the urban poor and rural population of India stand to benefit most from laparoscopy, owing to the shorter recovery times and reduced post-operative pain. The American and French positions have been described for laparoscopic cholecystectomy. Studies on ergonomics in laparoscopy deal mainly with issues related to the operating surgeon. There is not much literature on the issues faced by the team members during laparoscopy, especially in resource constrained settings. The authors propose a modification of the American position for LC, which enhances comfort and vision for the scrub nurse and also helps the surgeon guide the novice staff in LC.